O fotojornalismo durante o regime militar: imagens de Evandro Teixeira - Fávaro, Armando (2009)
In this project we intend to examine the creation process and the importance of photojournalism as a form of interaction and, therefore, the role it played during the Brazilian military dictatorship. With epistemological and theoretical fundaments built on the foundations of critical genetic and supported by peircean line semiotics, this study examines the creative process of photojournalist Evandro Teixeira, between 1964 and 1969, with your images and creativity, dribbled the repression and control apparatus placed on the streets and in the media by the regime of the military generals. His work challenges, thus, intolerance and social policy and demonstrates photography s crucial informative role as an instigator of reflection. The work also examines the importance of an integrated relation in terms thought in the process of creating a daily newspaper and selection through which goes every journalistic photo, especially Evandro Teixeira s images produced for the Jornal do Brasil. The process perspective approach is essential in the development of this study; it allows to more accurately examining photojournalism as well as its role in the collective journalism production network